Evaluating the Acceptance and Success of Mobile Banking Systems Using a Combination of UTAUT2 and Delone & McLean Models - Khairun Nisak, Novrinda; Ibrahim, Ali; Ermatita (Journal of Applied Informatics and Computing, 2025)
Mobile Banking is a digital banking innovation designed to facilitate financial transactions, payments, and account management. However, ensuring that the application meets user expectations remains a challenge. Based on Playstore reviews, 30% of users reported various obstacles, particularly difficulty accessing the app, leading to transaction failures. This study aims to see what factors affect user satisfaction. The research employed the SemPLS method, chosen due to its ability to handle complex models with multiple latent variables and assess intricate relationships between constructs. SemPLS is particularly useful for exploratory research and allows analysis without strict assumptions regarding data distribution. Data were collected from 382 respondents, determined using the Lemeshow formula. Validity was tested using factor loading (≥0.7), while reliability was confirmed through Cronbach’s Alpha and Composite Reliability (CR) ≥0.7.The findings indicate that human factors significantly impact user satisfaction, contributing 43.6% base R-Square value. Key influencing factors include Price Value, Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation, Facilitating Conditions, Habits, and Behavioral Intentions. Among these, Effort Expectancy, which represents ease of use, plays a crucial role in user satisfaction.To improve user experience, it is recommended to enhance access speed by optimizing server performance, reduce transaction failures through system stability improvements, and integrate AI-driven customer support for real-time troubleshooting. Future research could explore the role of trust and security perceptions in increasing user satisfaction and loyalty. These findings emphasize the importance of considering human aspects in digital service development to create a seamless and efficient banking experience.